Novel approach for high secure and high rate data hidden in the image using image texture analysis - Majeed, A. (Engg Journals Publications, 2009)
Steganography is the idea of hiding private, sensitive data or information within something that appears to be nothing but normal. If a person views the digital object that the information is hidden inside, he or she will have no idea that there is any hidden information, therefore the person will not attempt to decrypt the information, this is the main objective behind steganography. In this paper we extend a work approved two approaches from LSB algorithm; the 3-3-2 approach without any limitations on the type of images being used and can reach up to 33.3 of size of hidden data, and the second one is the 4-4-4 approach which increase the amount up to 50 of hidden data from the size of image but with certain limitations on the type of images, the new approach features will increase the data hidden in the image by merge the above approaches. Image texture and edge detection has been involve to appoint the appreciate sample from the image with the suitable approach.